1976
DOI: 10.1007/bf00965635
|View full text |Cite
|
Sign up to set email alerts
|

The breakdown of myelin-bound proteins by intra- and extracellular proteases

Abstract: Changes in protein components of purified myelin were measured following incubation in vitro with purified intra- and extracellular enzymes. Incubation with calf brain cathepsin D did not result in a significant relese of acid-soluble peptides as measured by ninhydrin analysis but was accompanied by a large loss of myelin proteins as determined on SDS-acrylamide gels. After 5 hr at 37°C there was a loss of about 25% for fast and slow basic proteins and the Agrawal proteolipid, but only a 5-10% loss for the Fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

1978
1978
2000
2000

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 42 publications
1
15
1
Order By: Relevance
“…Many studies have shown that acid proteases and other lysosomal enzymes are increased around active MS plaques (3-9, 36, 37) and in the central nervous system in EAE (10)(11)(12)(13)(14)(15). The increase in acid proteases in plaques correlates with the decrease in BP (5,6) which is known to be readily digested by proteases (13,38,39). However, neutral and acid protease activities were elevated to a similar degree in the spinal cord of rats with EAE (40).…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have shown that acid proteases and other lysosomal enzymes are increased around active MS plaques (3-9, 36, 37) and in the central nervous system in EAE (10)(11)(12)(13)(14)(15). The increase in acid proteases in plaques correlates with the decrease in BP (5,6) which is known to be readily digested by proteases (13,38,39). However, neutral and acid protease activities were elevated to a similar degree in the spinal cord of rats with EAE (40).…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that the myelin membrane contains an endogenous neutral protease that degrades myelin basic protein (MBP) (Marks et al, 1976;Smith, 1977; and myelin-associated glycoprotein (MAG) (Sato et al, 19840). The enzymatic degradation of myelin proteins was not inhibited by EGTA (Sato et al, 1982) unless the myelin was solubilized with Triton X-100 (Sato and Miyatake, 1982;Sat0 et al, 1984a), indicating that the protease must be bound to a hydrophobic site of the myelin membrane, and activation of this protease must be dependent on the myelin-endogenous calcium ion.…”
mentioning
confidence: 99%
“…Similarly, an increased susceptibility of Po glycoprotein to proteolytic enzymes results from partial lipid extraction of PNS myelin . Marks et al (1976) have reported that breakdown of lyophilized myelin by proteolytic enzymes is double that of fresh myelin. The interactions of the various constituents, therefore, appearo to protect partially the more vulnerable components, and disruption of these interactions increases the possibility of damage.…”
Section: B Enzymes and Myelin Destructionmentioning
confidence: 99%
“…MBP has since been shown to be easily degraded by many proteolytic enzymes (reviewed by Smith, 1977b), and the ease of peptide production has facilitated the elucidation of its amino acid structure. A number of investigators have shown that incubation of whole myelin with acid protease (Marks et al, 1976;Smith, 1980c), trypsin Banik and Davison, 1974), plasmin (Cammer et al, 1978b), or elastase (Smith, 1980c) results in extensive loss of MBP with much less effect on PLP. Recent evidence has appeared that the myelin-associated glycoprotein (MAG) mayaiso be a vulnerable component of myelin.…”
Section: Specific Cns Myelin Vulnerabilitymentioning
confidence: 99%